Assessing potential driving factors of the ecosystem service value of mariculture shellfish in China using a structural equation modeling approach - Gu, Yixin; Wang, Lifei; Lyu, Shaoliang; Dong, Jianyu; Liu, Bilin; Wang, Xuefeng (Frontiers in Marine Science, 2023)
China is one of the major mariculture countries for shellfish in the world and provides more than 70% of the total global shellfish production. However, there is limited knowledge of the potential driving factors of the ecosystem service value of mariculture shellfish in China. Understanding what factors and how they drive the ecosystem can provide reference for further improving the ecosystem service value of mariculture shellfish, which is both theoretically and practically important for promoting the development of marine fishery economy in China. In this study, data of six major mariculture shellfish species in nine coastal provinces of China from 2009 to 2020 were analyzed using a structural equation modeling approach to quantify the effects of resource distribution characteristics and market demand on the ecosystem service value of mariculture shellfish in China. The results indicated that both resource distribution characteristics and market demand are important driving factors of the ecosystem service value of mariculture shellfish in China. Specifically, from the perspective of path coefficient, market demand plays a more important role (0.58) than resource distribution characteristics (0.36) in influencing the ecosystem service value of mariculture shellfish in China. Therefore, the research results for shellfish marine culture can be summarized as: (1) to actively respond to changes in shellfish market demand, (2) to enhance development planning for coastal shellfish cultivation area, and (3) to strengthen systematic management of mariculture shellfish resources. Results of this study could provide theoretical support and serve as a basis for promoting sustainable development of shellfish culturing industry and fisheries economy in China.